Variation of the liquid film thickness distribution between contacting twin air bubbles during the coalescence process in water and ethanol pools. (July 2016) - Morokuma, Takayuki; Utaka, Yoshio
Highlights: Liquid film thickness formed between coalescing twin air bubbles were measured. Modified laser extinction method was used for precise film thickness measurement. The liquid film could be measured with an accuracy of ±0.06 μm for ethanol. Tendencies vary depending on configuration of liquid film thickness distribution. Film thickness ranged 0.2–2.5 and 0.1–1.0 μm for water and ethanol, respectively. Abstract: This study aims to investigate the characteristics of coalescence phenomena by precise measurement of the liquid film thickness distribution between approaching bubbles. This study targeted the coalescence of bubbles in pure water and ethanol pools to reveal the rupture characteristics of the liquid film formed between the approaching bubbles, which has a direct correspondence to the occurrence of coalescence phenomena. In this study, new and more precise measurements were performed for water and ethanol, whose physical properties are greatly different from one another. The basic experimental system, in which the approach velocity was easily controlled, was chosen to realize precise measurement of liquid film behaviors. That is, the coalescence of horizontally contacting twin bubbles was experimentally investigated using isothermal air–water and air–ethanol systems. The liquid film thickness formed between the contacting bubbles was measured using an improved laser extinction method. The variation of liquid film thickness between the bubbles at the rupture location and the distribution of the liquid film thickness were evaluated. The experimental parameters were the airflow rate and the measurement position for both water and ethanol. The bubble approach velocity and the contact duration, which is the time from the start of the bubbles' collision to the commencement of coalescence, were measured. When relatively quick bubble coalescence (short contact duration) occurs, the liquid film thickness is thinnest near the film center. The thinnest film thickness appeared just before coalescence and was approximately 1.0–2.5 μm and 0.3–1.0 μm for water and ethanol, respectively. An annular-shaped thinner area in the liquid film emerged and shifted from the center toward the periphery of the liquid film with the increase in the bubble approach velocity and short contact duration. The thinnest liquid film thickness just before the commencement of rupture in the ring-shaped areas was approximately 0.2–0.9 μm and 0.1–0.3 μm for water and ethanol, respectively. Trends of film thickness variation were qualitatively similar to each other for water and ethanol.